Effect of Compound (NPSB) Fertilizer Type on Yield and Nutrient use Efficiency of Maize (Zea mays L.) at Beko Village in Yeki District, Southwest Ethiopia - Mulisa Abdi Wedajo; Selamyihun Kidanu; Alemaheyu Reggasa (International Journal on Food, Agriculture and Natural Resources, 2023)
Farmer in different parts of Ethiopia uses a similar type of fertilizer and amounts that are below the crop requirements, even the low soil fertility which limits crop production in general. To solve the over-blanket fertilizer application over different agroecology Ethiopian Soil Information System (EthioSIS) mapped the soil fertility and recommended types of fertilizer for a specific location. A NPSB type of fertilizer where recommended for Beko village, but the rate of this fertilizer type was not studied so far. So, this field experiment was conducted to determine the rate of NPSB fertilizer type and nutrient use efficiency of maize during the 2018 cropping season. A total of eight treatments with four replications were laid out in a factorial randomized complete block design. Treatments were control (zero fertilizer), previously blanket recommended nitrogen and phosphorus (92 N+ 69 P2O5) kg/ha, 150 NPSB +100 urea +100 K2O kg/ha, 200 NPSB +100 urea + 100 K2O kg/ha, 250 NPSB +100 urea +100 K2O kg/ha, 150 NPSB +150 urea +100 K2O kg/ha, 200 NPSB +150 urea +100 K2O kg/ha and 250 NPSB +150 urea +100 K2O kg/ha. Data were statistically analyzed by statistical analysis system (SAS) and mean treatment differences were compared by least significant differences (LSD). An analysis of variance indicated that application of NPSB fertilizer was not influenced plant height, ear height, ear length, cob length, number of ears per plant, thousand seed weight, harvest index, and shelling percentage as compared to the previously blanket recommended Nitrogen and Phosphorus (NP) fertilizer but grain and above-ground dry biomass were influenced except the application of 150 NPSB +100 urea. Application of 250 NPSB + 100 urea gave the highest maize grain yield (8828.2 kg/ha). Application of NPSB fertilizer improved the nitrogen and phosphorus use efficiency of maize compared to the previously blanket recommended NP. The highest N use efficiency (64.75 kg/ha) was obtained from the application of 200 NPSB +100 urea, while the lowest N use efficiency (23.89 kg/ha) was from the previously blanket recommended NP fertilizer. As economic analysis indicated that the application of 150 NPSB +100 urea is recommended for the study area.